Labour Mobility From The Plantation Sector And Some Of Its Socio-Economic Implications - Govindasamy, Nathan (Universiti Sains Malaysia, 1982)
The scope of this graduation exercise has been limited to two case studies of rubber and oil-palm estates probing the issue of labour mobility in the plantation sector and some of its socio-economic implications. The research conducted elucidated facts and figures which well augurs for the claims of labour shortages in the plantation sector. One obvious implication is that the labour shortage situation in the estates stand to be aggravated in the future. Out-migration from the estates that has occured during the past five years had lost the most productive members of the labour force. This coupled with the fact that a considerable number of estate residents were found to be commuters shows that the estate labour force is being absorbed into the modern industrial sectors which are fast expanding in areas surrounding the estates. Even among the commuters, it was found that the persons of young adult age were the ones who were commuting. These people possessed minimum levels of education and were mostly single.